SIKAP KONSUMEN TERHADAP JASA LEASING UNTUK MOBIL Studi Kasus Pada PT. Kencana Internusa Artha Finance Komplek Ruko Casa Grande No. 14 Maguwoharjo Depok Sleman Yogyakarta - Dedy Putra Pamungkas (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2013)
This study aims to determine consumer attitudes at PT. Kencana Internusa Artha Finance. To determine consumer attitudes toward variable leasing services that include credit period, credit standards and billing policy. The research was carried out directly by the researcher with the consumer of PT. Kencana Internusa Artha Finance. To determine consumer attitudes towards leasing services for automobile use Multiatribut Attitude Model analysis techniques. In this study , the data collected by questionnaires. The population was consumers of PT. Kencana Internusa Artha Finance. The sample of 100 respondents who used Accidental Sampling method. Based on calculations indicate that consumer attitudes toward credit period is a significant attribute, consumer attitudes toward credit standards is a significant attribute and consumer attitudes toward attributes are significant in the billing policy. The result showed there are consumer attitudes towards services for car leasing is positive (very well) where his Ab by using the Multiatribut Attitude Model techniques of 18,64, this means that attitude or response of consumers as a whole has to meet what is expected and what is believed to consumers. So we can say for the car leasing services in PT Kencana Internusa Artha Finance is in conformity with what consumers want. Keywords : Consumer attitudes, credit period, credit standards, collection policy